The Chickpea Is Anti-Microbial: Review Study (International Journal of Innovative Research in Engineering & Management, 2021)
Antibiotic resistance is serious global problem. Many  commercial antibiotics due to over use have induced some  microbes to become multi drug resistant. Tetracyclines are  important bactericidal agents towards various bacteria.  Resistance towards tetracyclines includes factors like intrinsic,  adaptive & mutational modes. Thereby many researchers are  gravitating towards searching for novel anti-microbial agents  from the natural world. In this paper, the resistance towards  tetracyclines have been briefly stressed upon along with the  evaluation of the anti-microbial role of Chickpea (Cicer  arietinum) towards a set of bacteria. Bacteria, Klebseilla &  Bacillus subtilis were grown as a lawn culture that was then  exposed to varying concentrations of butanolic & aqueous  extracts. After 24 hours, the butanolic extract showed higher  activity as compared to the aqueous extracts. However,  Sumycin showed the highest activity. This result has given  hope that novel anti-microbial agents can be isolated from this  plant.
Keywords: Anti-microbial resistance; Anti-microbial agents; aqueous extract; butanolic extract; Chickpea (Cicer arietinum)